THE INFLUENCE OF DIGITAL LITERACY AND KNOWLEDGE OF FIQH MUAMALAH ON THE DESIRE TO BE A DROPSHIPPER IN BUYING AND SELLING PRACTICES ON E-COMMERCE PLATFORMS - Widiarni, Anis; Anshori, Aiyub; Susanto, Dedy (Tujjar International Journal of Islamic Economics Development, 2024)
E-commerce and digital marketing-based businesses have become a routine for entrepreneurs to run their businesses, which involve buying and selling systems and transactions online through the use of e-commerce platforms. In utilizing the e-commerce platform, which can foster the community for entrepreneurship, it is necessary to conduct research to analyze the effect of digital literacy and religious knowledge on the dropshipper's desire to practice buying and selling on the e-commerce platform. This study uses a quantitative method, which is a process to find the results of knowledge in the form of data. as a medium for analyzing information regarding what is sought in this study. By means of collection techniques and data collection tools sourced from the population (dropshipper) in the city of Pontianak, through an online form filled in by a questionnaire, the population being an indicator sample of 30 people. Which will later be collected and analyzed based on predetermined methods to determine the contents of the problem formulation in this study. Based on the results of the study, it can be seen that the T Statistic value of the effect of Digital literacy on the desire to become a dropshipper is 0.957, so the T statistic is 0.05. It can be seen that Ha: the influence of digital literacy has no significant effect on the desire to become a dropshipper. Based on the research results, it is known that the T statistic value of muamalah fiqh knowledge on the desire to become a dropshipper is 3.787, so the T statistic > 1.96. The P value is 0.000, so the P value < 0.05. It can be seen that Ho: muamalah fiqh knowledge has a significant effect. on the desire to become a dropshipper. The effect of digital literacy has no significant effect, which means that respondents who are running a business with a dropshipper system assume that the effect of digital literacy has no effect on buying and selling practices on the commerce platform, and muamalah fiqh knowledge is very influential, which means that respondents who are running a business with a dropshipper system assume that muamalah fiqh knowledge is very influential on buying and selling practices on the e-commerce platform.